159 The effect of sire FEC EBV on parasitism and survivability in grazing Katahdin lambs. (28th November 2020) - Weaver, Andrew R; Burke, Joan M; Morgan, Jim; Wright, Donald L; Greiner, Scott P; Bowdridge, Scott A
Abstract: Selection for reduced fecal egg count (FEC) is an important management tool to combat anthelmintic resistance in worm populations. To understand consequences of selection for parasite resistance, a divergent mating scheme was established whereby Katahdin rams with high (HiFEC; n = 4) or low fecal egg count (LoFEC; n = 4) estimated breeding values (EBV) were randomly mated to ewes at the Southwest Virginia AREC. Mid-March born lambs (n = 199) were managed as one group until approximately 120 days of age (Weaning: June 4). Beginning at 45 days of age, BW and FAMACHA scores were collected weekly. Deworming occurred as necessary (FAMACHA ≥ 3) and fecal egg counts were taken biweekly. Statistical analysis was performed using SAS with fixed effects of sire EBV type. Fecal egg count was significantly higher in HiFEC-sired lambs one week prior to weaning (665 vs. 427 eggs/g, P < 0.05) and again at three (3398 vs. 2175 eggs/g, P < 0.01) and five (3596 vs. 2209 eggs/g, P < 0.01) weeks post-weaning. These FEC differences corresponded to differences in lamb weaning and post-weaning FEC EBV (43% vs. -43%, P < 0.05 and 82% vs. -66%, P < 0.01; respectively). Lambs sired by HiFEC-rams required more anthelmintic treatment than LoFEC-selected lambs (76% vs. 61%, P < 0.05). The weaning and post-weaning FEC EBV of HiFEC-sired lambs was greater in lambs that died than those that survived to 120 d (37% vs. 83%, P < 0.01 and 73% vs. 138%, P < 0.01; respectively); however, this phenomenon did not occur in LoFEC-sired lambs. Taken together, these data indicate that LoFEC-sired lambs have reduced parasite burden and are more likely to survive to weaning. Thus, sire selection for low FEC EBV can have indirect effects on lamb survival and general immunity.